Resolution of the Marthasterias Taxonomic "Disar-star" - Wright, Amy G (Department of Biological Sciences, 2014)
Marthasterias glacialis is a sea-star found in the cool-temperate waters of the north-eastern Atlantic as well as along the south-western tip of Africa. The South African Marthasterias population is comprised of two distinct morphotypes, a smooth, spineless rarispina form and a spiny africana form. These distinct morphotypes have been variably described as separate species, subspecies or forma by various authors over the last century. To test whether these two morphotypes are separate species, or part of a single distinct South African clade, 78 Marthasterias individuals were collected from the Cape Peninsula of South Africa. Morphological comparisons were carried out between individuals of the two forms and the results showed no significant clustering of samples. This indicates that there is no morphological separation of the forms into distinct species. The africana and rarispina forms were also shown to be genetically indistinguishable, using both a mitochondrial COI sequence and a nucleic ITS1 gene. The COI and ITS sequences of the South African specimens were also compared to that from European specimens, and the p-value distances of 4% and 3% respectively show a significant distinction between the two clades. The South African Marthasterias is thus genetically distinct from the European M. glacialis, and as such, Marthasterias africana sp. nov. will be formally described as a new species elsewhere. M. glacialis has a spine armament pattern of a series of three regular rows of spines down the length of each arm, whilst Marthasterias africana sp. nov. is either covered in many irregularly-spaced spines, or has an extraordinarily bare surface of only two spine rows per arm. M. africana sp. nov. may also have an actinal spine simulating the presence of a third inferomarginal spine. This work resolves a century of taxonomic dispute, separation and amalgamation of the two forms and establishes that will for part of a single, uniquely South African, Marthasterias species that is distinct from the European M. glacialis.